PESONA WISATA KOTA BATAM DAN PANDEMI COVID 19 - Dailami Muslim; Thandzir, Mohammad (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2022)
Development of Batam City began with the establishment of the Batam Authority Agency with the issuance of Presidential Decree No. 41 of 1973 concerning the Batam Island Industrial Area, which is currently the Batam City Concession Board. Batam City which is part of the special Batam-Bintan-Karimun (BBK) free trade zone area has a very strategic location, located on international shipping lanes which have a long distance. very close and directly adjacent to the Singapore Strait and the Malaysia Strait. The city of Batam has grown and developed into a modern city that has international standard infrastructure facilities, which was originally designed as an industrial city, until now it has also been developed into a national strategic tourist destination city. Due to its strategic location, supported by good infrastructure facilities, Batam City is a prima donna for domestic and foreign tourists. According to data from the Batam City Government, the number of tourist visits in 2019 before the Covid 19 pandemic hit reached 6 million domestic tourist visits and 1.9 million foreign tourists. The Covid 19 pandemic that has hit all countries in the world has knocked down the tourism sector of Batam City due to the implementation of health quarantine by every country with restrictions on people's movement and gathering. hard so that the spread of the Covid 19 corona virus in Batam City can be stopped. The Batam City Government has also succeeded in carrying out the Covid 19 vaccination program well. By being able to handle the spread of Covid 19 so that the entrance and exit of neighboring countries will be opened, the Batam tourism sector will be able to be boosted again, and the economy of Batam City will rise.